INFORMATION SEARCHING BEHAVIOR OF INTERNATIONAL SPECIAL COLLECTIONS AT THE UNIVERSITY OF INDONESIA LIBRARY - Izzati, Dafina Rossa; Samosir, Fransiska Timoria; Widiyarti, Diyas (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Users of the Foreign Language Special Collection Service at the University of Indonesia Library consist of various groups, the majority of whom are students, including foreign students, students from the University of Indonesia (UI), and students from outside UI. They use this service to meet their information needs related to the foreign language special collection. In the information search process, users follow eight stages, namely starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. Users directly utilize the available collections to meet their diverse information needs. These differences in needs give rise to variations in information search behavior among users. In addition to utilizing existing collections, users also often ask for help and consultation from librarians. This study aims to understand the information search behavior related to the foreign language special collection at the Special Collection Service at the University of Indonesia Library. The approach used in this study is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the information search behavior of users at the Foreign Language Special Collection Service at the University of Indonesia Library includes the stages of starting, chaining, browsing, differentiating, extracting, monitoring, verifying, and ending. These stages are carried out to meet specific information needs, both for academic assignments, personal needs, and exploration of foreign language literature and literature. Users do not only rely on internal library services but also utilize external information sources such as Google, websites, and other search engines. This study provides a deeper understanding of the dynamics of information needs and user behavior patterns in utilizing special foreign language collections, and highlights the importance of librarian assistance services in supporting the information search process effectively. Library managers should improve the technological infrastructure that supports information searches, such as updating and simplifying the OPAC (Online Public Access Catalog) system and integrating search services with popular search engines. With this innovation, it is hoped that users can find the information they need more easily and quickly.